Hubungan Pola Makan Dengan Kejadian Anemia Pada Remaja Puteri Di SMAN 1 Kelumpang Tengah - Aspihani, Gt. Maryam; Kabuhung, Elvine Ivana; Ulfa, Ika Mardiatul (Pusat Riset dan Inovasi Nasional, 2023)
The large incidence of anemia cases in female students shows that there is still a lack of iron (Fe) nutrient consumption in adolescent girls. The onset of anemia can be caused by the intake of the wrong diet, irregular and unbalanced with the adequacy of nutritional sources needed by the body. The purpose of the study was to determine the relationship between diet and the incidence of anemia in adolescent girls. Analytical survey research method with cross sectional approach. The sample in this study used a total sampling of 46 people. Data collection comes from primary data, namely the results of questionnaires analyzed using the chi square test. The results of the study were mostly adolescents with poor diet as many as 21 people (45.7%), adolescent girls with anemia as many as 24 people (52.2%). There is a relationship between diet and the incidence of anemia in adolescent girls (p value = 0.000<0.05). The conclusion of this study is that food consumed by adolescent girls does not have the number of calories and nutrients that are in accordance with needs such as carbohydrates, fats, proteins, vitamins, minerals, fiber and water so that their nutritional status cannot be fulfilled so that it can cause anemia.